Voice in an Iron Box: The Development of Public Communication Through Coin-operated Public Telephones in Jakarta 1980-2012 - Arvianti, Sevita; Wibowo, Eka Yudha (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The development of coin payphones in Jakarta in 1980-2012 reflects a significant transformation in the communication patterns of urban society. Coin payphones were introduced as an affordable communication access solution, becoming an integral part of the daily lives of Jakarta residents, from small traders to families. This study examines the history and social impact of coin payphones, which function as an inclusive means of public communication amidst rapid demographic growth. In the 1990s, coin payphones were once a public favorite, but along with the emergence of mobile phones, people began to abandon coin payphones so that their use began to decline. This study uses a historical research method consisting of heuristics, source criticism (verification), interpretation, and historiography. Through historical research, this study will identify factors that influence the popularity and decline of coin payphones, including vandalism and the transition to digital communication. The results of this study are expected to contribute to the historiography of communication in Indonesia, as well as become a reflection material for public policy related to the preservation of city artifacts and documentation of technology that once played an important role in the social life of society.